Role of Neuropsychological Ability in Predicting Psychological Wellbeing Among Stroke Patients - Ms. Sundus Bibi; Dr. Syeda Razia Bukhari (Review Journal of Social Psychology & Social Works, 2024)
The aim of the study was to explore the Role of Psycho neurological ability in predicting psychological wellbeing among stroke patients. This study aims to understand how the stroke patient’s neuropsychology and psychological wellbeing impaired and how they suffer. The goals of the present research were that 1) What is the effect of psycho neurological abilities on psychological well-being of stroke patients 2) What are the demographic differences on psycho neurological ability in psychological wellbeing among stroke patients. A sample of 100 participants, including males and females both was selected were recruited from a hospital Hayatabad Medical complex, Rehman Medical college Peshawar. Data was collected through purposive sampling technique and 100 participant’s data were utilized for research based on psycho neurological ability and psychological well being among stroke patients. bender gestalt tests (Carver, 1997) and psychological wellbeing scale (PWBS) by (Bejerot et. al., 2014) were used to measure the research variables. Descriptive statistics, linear regression and independent sample t-test analysis was applied for research data analysis on SPSS (V 23.0). It was hypothesized that there would be a negative impact of psycho neurological impairment on psychological wellbeing among stroke patients. Results indicates same relationship between study variables There would be a demographic difference (gender, family system, age, socio economic system) on psycho neurological ability and psychological well-being among stroke patients. Likewise, significant gender differences were indicated between studies variables in which male have high significance difference as compared to females. Result also indicated that there is no significant difference of socio economic difference.